Photocatalytic Activities Enhanced by Au-Plasmonic Nanoparticles on TiO2 Nanotube Photoelectrode Coated with MoO3 - Chia-Jui Li; Chuan-Ming Tseng; Sz-Nian Lai; Chin-Ru Yang; Wei-Hsuan Hung (Nanoscale Research Letters, 2017)
Abstract Although TiO2 was formerly a common material for photocatalysis reactions, its wide band gap (3.2 eV) results in absorbing only ultraviolet light, which accounts for merely 4% of total sunlight. Modifying TiO2 has become a focus of photocatalysis reaction research, and combining two metal oxide semiconductors is the most common method in the photocatalytic enhancement process. When MoO3 and TiO2 come into contact to form a heterogeneous interface, the photogenerated holes excited from the valence band of MoO3 should be transferred to the valence band of TiO2 to effectively reduce the charge recombination of photogenerated electron–hole pairs. This can efficiently separate the pairs and promote photocatalysis efficiency. In addition, photocurrent enhancement is attributed to the strong near-field and light-scattering effects from plasmonic Ag nanoparticles. In this work, we fabricated MoO3-coated TiO2 nanotube heterostructures with a 3D hierarchical configuration through two-step anodic oxidation and a facile hydrothermal method. This 3D hierarchical structure consists of a TiO2 nanotube core and a MoO3 shell (referred to as TNTs@MoO3), as characterized by field emission scanning electron microscopy and X-ray photoelectron spectroscopy.